Description of three new species of Nemapalpus (Diptera, Psychodidae, Bruchomyiinae) from Atlantic Forest in southeastern Brazil - Santos, Claudiney Biral Dos; Falqueto, Aloísio; Alexander, Bruce (Zootaxa, 2009)
Three new species of Nemapalpus were collected by CDC light traps in Atlantic Forest in the Brazilian state of Espírito Santo. They are described here as Nemapalpus brejetubensis, N. espiritosantensis and N. capixaba.